Education Sector COVID-19 Response Plan and Its Implication on Inclusive Education in the Gambia - Abdou Barrow (Universitas Teuku Umar, 2022)
During the early hours of 2020, COVID -19 terrorized the world by forcing many countries to close their borders and restrict internal movement by imposing a state of national emergency which was geared toward lockdowns for months in some areas for years. The Gambia was not an exception to this trajectory and one of the sectors heavily stroked by this lockdown was education. As a result, “the Ministry of Basic and Secondary Education (MoBSE)” designed a Response framework to curb learning loss across the country. This study aimed to analyse the policy and describe the implication it has on inclusive education. The qualitative research method was used imploring the interpretive approach in the analysis. Despite the nobility and ambitiousness of the policy, the findings from the analysis revealed that the policy had a serious blind spot in the area of inclusion because many children are left out because of their inability to access the mediums where lessons are delivered. Many households in rural Gambia did not have a stable electricity supply or even own a television or radio set, therefore it was impossible for children in these communities to benefit from the program. In addition, children with special needs are also excluded particularly does who are visually or hearing impaired.